Application of geotechnical database in the city of Athens (Journal of Nepal Geological Society, 2000)
The paper presents a relational geotechnical database management system, which can accommodate the information derived from geotechnical investigation. It was built in Microsoft® Access environment at the Geotechnical Division of National Technical University of Athens (NTUA). Two examples of its application through Microsoft® Excel and Arcview® version 3.1 are also given.